PENGARUH EDUKASI GIZI DENGAN MEDIA KOMIK DAN VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN TENTANG OBESITAS PADA REMAJA DI SMA NEGERI 98 JAKARTA - Olla Wilda Nasyiba (2022)
Background : Obesity is currently being a global health problem. In 2018, adolescents in Indonesia between the ages of 13 to 15 years who suffered from obesity reached 16 percent and 13,5 percent between the ages of 16 to 18 years were 13.5 percent. One of the efforts to prevent and lower the obesity rate among adolescents is through nutrition education. Objective : This study aimed to find the effect of nutrition education using comic and animated video on obesity knowledge level among the adolscents at 98 Public Senior High School Jakarta. Method : The research used a quasy experimental (pseudo-experiment) design with pre test dan post test group involving 62 students from the second and third grades which selected through the cluster random sampling technique. The data were collected with an online method. Result : The result showed a significant difference in respondents' knowledge of the comic group (p=0,000) and the animated video group (p = 0,000). Conclusion : The result of the Wilcoxon test showed a significant effect of nutrition education using comic and animated video on obesity knowledge level among the adolescents at 98 Public Senior High School Jakarta.